α-Imino gold carbene intermediates from readily accessible sulfilimines: intermolecular access to structural diversity - Tian, Xianhai; Song, Lina; Hashmi, A. Stephen K. (Chemistry - a European journal, 2020)
Abstract Catalytic approaches to pharmaceutically important bioactive skeletons through gold carbene intermediates have experienced a dramatic development in the last decade. Although various carbene precursors continue to play an important role in heterocyclic syntheses, these reagents are associated with some drawbacks in terms of functional group tolerance, synthetic methods and safety limitations. A new generation of nitrene transfer reagents was established in 2019: the sulfilimines. These are safe, inexpensive and readily available. They can conveniently be stored and handled, and thus represent ideal reagents for the fast and modular modification of scaffolds and the preparation of libraries by intermolecular reactions of two components. Both the practical methods for synthesizing sulfilimines and the versatility of these ylidic species in gold-catalyzed preparation of structural diversity, for both heterocycles and carbocycles, will be outlined in this Concept article.